Prevalence of Screening in Patients Newly Diagnosed with Colorectal Cancer in Ontario - Chelsea Taylor; Susan E Schultz; Lawrence F Paszat; Susan Bondy; Linda Rabeneck (Canadian Journal of Gastroenterology)
OBJECTIVES: The primary objective was to determine the proportion of individuals with a new diagnosis of colorectal cancer (CRC) in Ontario in whom the cancer was screen detected. The secondary objectives were to determine the cancer stage at diagnosis and the indications for the procedure in patients who received their first colonoscopy.